2017
DOI: 10.15666/aeer/1501_127139
|View full text |Cite
|
Sign up to set email alerts
|

Invasion of Abandoned Agricultural Fields by Acacia Mearnsii Affect Soil Properties in Eastern Cape, South Africa

Abstract: Abstract. Abandoned agricultural fields are susceptible to alien plant invasion because they experienced intensive anthropogenic activities. However, there is limited studies on soil physicochemical changes in alien plant invaded abandoned agricultural fields in comparison to uninvaded abandoned agricultural fields and natural sites. This comparative study explores soil physico-chemical changes in ten-year-old abandoned agricultural fields invaded by Acacia mearnsii in comparison to ten-year-old uninvaded aban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…Besides, the canopy of both natural and Acacia species has the potential to provide shelter for soil moisture thus making it high upon being captured by litter (Mugunga and Mugumo, 2013). The removal of A. mearnsii is expected to cause soils to become less repellent given that some studies have shown that invasion by A. mearnsii causes soils to be repellent (Ruwanza, 2017). Contrary, results of this study showed that soils in cleared areas were strongly repellent with the bulk being slightly repellent.…”
Section: Discussioncontrasting
confidence: 61%
“…Besides, the canopy of both natural and Acacia species has the potential to provide shelter for soil moisture thus making it high upon being captured by litter (Mugunga and Mugumo, 2013). The removal of A. mearnsii is expected to cause soils to become less repellent given that some studies have shown that invasion by A. mearnsii causes soils to be repellent (Ruwanza, 2017). Contrary, results of this study showed that soils in cleared areas were strongly repellent with the bulk being slightly repellent.…”
Section: Discussioncontrasting
confidence: 61%
“…Furthermore, they endanger indigenous flora by contributing to genetic contamination and the extinction of distinctive genetic features [ 13 ]. Invasive plants also impact ecosystem services such as water quality, pollination, and soil nutrient cycles [ 10 , 14 ]. While attempts to battle these invaders are underway, continued, and sustained action is required to maintain South Africa's ecosystems and alleviate the varied repercussions of invasive alien plant species.…”
Section: Introductionmentioning
confidence: 99%
“…Acacia mearnsii and Acacia dealbata are among the top 10 and 25 invading species, respectively, occupying approximately 2.5 million hectares of South African land [ 19 ]. Much research has focused more on these species due to their wider spread, rapid invasion rates, and potential environmental damage [ 14 ]. Determining the effectiveness of restoration efforts, assessing soil recovery, assisting in the establishment of native plants, managing soil nutrients, preventing reinvasion, and promoting long-term ecosystem resilience all depend on an understanding of the characteristics of the soil before, during, and after the removal of invasive species [ [21] , [22] , [23] ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations